Solar and lunar atmospheric tides in rainfall at Poona (MAUSAM, 1972)
The atmospheric tides in 'the rainfall data of the monsoon season, ...e., June to September at Poona (18° 32' N; 73° 51'E), have been studied by using hourly mean values and bi-hourly mean values for the period 1949-1960. Both solar and lunar effects upto the 4th harmonic have been discussed. Study of the variation with lunar phase of the rainfall indicates a maximum fall near the phase 3 while there is no other regular variation with lunar phase.